Labyrinth arrangement analysis based on image processing - Škrabánek Pavel (Springer, 2015)
The approach described in this paper has been developed as a supporting tool for practical exercises based on a teaching aid; however, its application is far from being limited to be used only in the education process. The main task of the approach is extraction of information about structure of a working environment from color images and its transformation to an appropriate form suitable for path-planning. The working environment considered in this paper is a labyrinth. Since the information is to be used further by path-planning, its expression in the form of a graph is required, or, more precisely, the adjacency matrix is required as the output. The transformation of the real world into a discreet representation is based on the exact cell decomposition in this approach. The approach employs the well-known image processing algorithms; however, the procedure of the labyrinth layout analysis as well as the transformation of the acquired information into the adjacency matrix has been developed and tested in this work. The approach has been realized and verified in MATLAB using the Image Processing Toolbox.
Analýza uspořádání labyrintu s využitím metod zpracování obrazu
Keywords: image processing, teaching aid, mobile robot, path-planning, graph, MATLAB, labyrinth building kit; zpracování obrazu, pomůcka při výuce, mobilní robot, plánování pohybu, graf, MATLAB, stavebnice bludiště